(untitled) (CIPEEX, 2026)
Work is appointed by Frankl (2020), precursor of logotherapy, as a possible way to reach a meaning of life, central category for human beings. In the present essay, that potential was evaluated based on interviews made with volunteers from an institution about their perceptions of meaning amidst their professional activities and their volunteer work. It was verified that meaning was perceived in both forms of occupation, although more difficulties were mentioned in formal work, while more autonomy and affect were attributed to volunteer activities.